New insights into the role of space on the microstructure and the development of strength of multicomponent cements. (August 2021) - Zajac, Maciej; Durdzinski, Pawel; Giergiczny, Zbigniew; Ben Haha, Mohsen
Abstract: The hydration, porosity, and compressive strength of cements at varying water/cement and limestone/cement ratios were investigated. Thanks to the broad range of the effective water/cement studied, new insights into the nature of the C–S–H phase and the basic mechanisms behind the formation of mechanical performance were gained. The mechanical properties of the main hydrated phase, the C–S–H, are governed by the available space. It was shown that the space available modifies the C–S–H microstructure, which in turn is reflected in the pore volume and porosity distribution. In high-porosity environments, a C–S–H with the higher amount of gel pores forms and efficiently fills the porosity. Contrarily, in low-porosity environments, the coarse microstructure forms. Furthermore, the available space has impact on the clinker reaction and chemical composition of the C–S–H. It was demonstrated that the available space alone is responsible for a part of the microstructure modifications ascribed to the pozzolanic and semi-hydraulic reactions. Highlights: Increasing w/c promote reaction of clinker. Starting w/c has pronounced impact on Ca/Si of C–S–H. Available space influences the pore size distribution. Mechanical properties of C–S–H are governed by available space.